The Rhetorical Structure of the Climax Plot in Ayat-Ayat Cinta by Habiburrahman El Shirazy (2004) - Nurfadilah; Andi Samsu Rijal; Warsidi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research examined the rhetorical structure of the climax plot in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy (2004). This study employed a qualitative design, utilizing Swales' (1990) move analysis method to identify moves and strategies in the climax chapters, and supported the analysis with narrative plot mapping. The results showed that the climax plot was dominated by rhetorical moves that highlighted narrative shifts through tension, provided character struggles, highlighted character emotions, and built a dramatic atmosphere that served to strengthen the ideological and persuasive dimensions of the narrative. In addition, a length analysis of the climax revealed that measuring it through the number of chapters, pages, paragraphs, and dialogues effectively reflected the dramatic effect and maximized the communicative impact on readers. These findings indicate that rhetorical structure influences the persuasive power of the climax in conveying moral, cultural, and religious values. This study provides insight into how narrative design contributes to the creation of meaning in Indonesian popular literature.